Characterization of Additive Blended Fuels on Single-Cylinder Motorcycle Engines - Olawale, Kazeem; Alimin, Ahmad Jais (Journal of Advanced Mechanical Engineering Applications, 2024)
Despite their potential, challenges such as corrosion, compatibility issues with older engines, fuel system problems, lower energy content, and increased fuel consumption persist. With the shift toward green technologies and sustainable energy, biofuels like ethanol are seen as promising replacements for depleting hydrocarbons. This study explores the impact of polyisobutylene additives in ethanol-gasoline blends to enhance their use in ICEs. Five test fuels with varying additive concentrations were formulated and designated as E5P100, E5P500, E25P100, E25P500, and E0P100. These fuels were examined for their physicochemical properties. E5P100 had the highest research octane number (RON 96.5), whereas E0P100 had the lowest (RON 95.5). E25P500, with the highest density (0.79342 g/cm³), had the lowest brake specific fuel consumption (BSFC) value (1.5 kg/kW-hr). The blend with the highest heating value (E0) had 43350 kJ/kg, providing more energy during combustion, which improves engine performance by increasing power output and ensuring smoother operation. Blends E5PIB500 and E25P500 showed the highest engine power (5.8 kW and 5.95 kW, respectively), significantly better than conventional gasoline (E0, 3.65 kW), leading to improvements in brake mean effective pressure (BMEP), brake thermal efficiency (BTE), and brake torque (BT). Additionally, E5P500, E25P100, and E25P500 reduced  and  emissions due to their higher ethanol and additive content. Conversely, E5P100 and E0P100, with lower ethanol and additive content, resulted in incomplete combustion, increasing  emissions at higher speeds. Overall, additive-blended fuels enhance combustion efficiency, reduce harmful emissions, and optimize engine performance, supporting green technologies and clean energy.